1967
DOI: 10.1159/000179595
|View full text |Cite
|
Sign up to set email alerts
|

Les tophus goutteux de la médullaire rénale des urémiques chroniques

Abstract: Les reins de 62 sujets morts au terme d’une insuffisance rénale chronique ont été examinés à la recherche de tophus. Dans 17 cas, des tophus avec ou sans précipitations cristallines intra-tubulaires ont été constatés, dans la médullaire exclusivement. Les tophus sont faits d’une nécrose centrale, entourée d’une réaction cellulaire, et limités par une coque scléreuse. Ces lésions sont aisément identifiables à I’examen de pièces fixées dans le formol à 10%. Après fixation alcoolique, on constate que la nécrose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1975
1975
1998
1998

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The authors who first described such an effect of a similar diet also advanced this hypothetical explanation [Walter et al, 1979], Another possibility refers to sUR. Chronic hyperuri cemia, due to causes other than renal failure, is well known to impair renal function and it is quite likely that also the severe hyperuricemia due to renal failure may exert the same effect [Verger et al, 1967;O.ttberg. 1968].…”
Section: Discussionmentioning
confidence: 99%
“…The authors who first described such an effect of a similar diet also advanced this hypothetical explanation [Walter et al, 1979], Another possibility refers to sUR. Chronic hyperuri cemia, due to causes other than renal failure, is well known to impair renal function and it is quite likely that also the severe hyperuricemia due to renal failure may exert the same effect [Verger et al, 1967;O.ttberg. 1968].…”
Section: Discussionmentioning
confidence: 99%
“…They have also been found at autopsy in the kidneys of patients with renal disease who have never suffered from gout, and Verger et al [2] reported their presence in 17 out of 62 patients who died with chronic renal failure. The renal microtophi in these cases were identical with those seen in the patients with primary gout and the authors attributed the development of microtophi in these patients to the hyperuricaemia associated with the chronic renal insufficiency [2,3], It should be stressed that these medullary microtophi differ from the intratubular deposits of uric acid which are not uncommonly seen in subjects with both primary and secondary overproduction of urate [4], Al though all the factors which contribute to the formation of medullary urate deposits are not precisely known, it is likely that the concentrations of urate in both the intra tubular fluid and the renal interstitium are important and that local conditions of pH and electrolyte concentration are optimal for urate crystal formation [5], Moreover, a progressive urate gradient has been demonstrated be tween the cortex and the papilla in the human kidney at autopsy [6] and studies in rhesus monkeys have indicated that, like that of urea, this gradient is dependent upon the antidiuretic state and is abolished by hydration. The present study was undertaken because casual observations of kidneys at autopsies in Brisbane, Australia, revealed a surprisingly high incidence of medullary urate deposits.…”
Section: Introductionmentioning
confidence: 94%
“…However, these reports largely antedated the availability of therapeutic agents for gout such as uricosuric drugs and allopurinol. Urate deposits also have been found in kidneys from patients with chronic renal failure, but without any history of symptomatic gout [25, 26], and urate precipitation can even occur in the renal medullas of normal individuals [27]. Gout also occurs as a relatively frequent complication of chronic renal failure, but usually becomes manifest after renal disease is well established.…”
Section: Spectrum Of ‘Chronic Hyperuricemic Nephropathy’mentioning
confidence: 99%